From Wall 1.0 to Wall 2.0: Graffiti, Social Media, and Ideological Acts of Resistance and Recognition Among Palestinian Refugees. (April 2018) - Li, Eric Ping Hung; Prasad, Ajnesh
Writing as an ideological act of resistance and recognition among members of the socially disenfranchised has been engaged with in myriad contested political and cultural terrains. Historically, for Palestinian refugees living under conditions of Israeli occupation, expressions of resistance and recognition were visually and textually inscribed through provocative displays of graffiti on the very separatist wall erected by their occupiers. More recently, however, these acts have been (re)articulated through various forms of social media. We capture this phenomenon as being one dimension of transmedia storytelling, and specifically as a consolidation of, what we are calling here, Wall 1.0 and Wall 2.0. We argue that this consolidation has engendered significant implications for how ideological acts of resistance and recognition among disempowered subjects ought to be conceptualized. Indeed, this consolidation marks a necessary move in the contest over place from geographically constrained physical spaces to spreadable and editable digital spaces. In terms of theoretical contribution, it has illuminated how discursive political claims are transitioning from a state of temporality and attributed ownership to a state of permanence and coproduction.